Extrahepatic bile duct ligation in broiler chickens: ultrastructural study of Ito cell - Ekowati Handharyani; K Ochiai; A Winarto (Jurnal Ilmu Ternak dan Veteriner, 2004)
The Ito cell (fat-storing cell) is a cell lying in perisinusoidal space of liver. The function of Ito cell is expanding from a site of fat-storing site to a center of extracellular matrix metabolism and mediator production in the liver. This study was performed in order to evaluate the Ito cells in cholestatic condition. The artificial cholestatic was conducted by ligation of extrahepatic bile ducts (bile duct ligation = BDL) in broilers. The results showed that BDL induced bile congestion, fibrosis, proliferation of Ito cells and intrahepatic bile ductules. Immunohistochemistry demonstrated that Ito cells were scattered throughout the fibrotic areas, and larger in size with more extensive immunoreactivity than those in normal livers. Ultrastructural study demonstrated that Ito cells were closely associated with the production of extracellular collagen fibers. Ito cells actively react against hepatocytic injuries, especially in fibrogenesis of cholestatic livers.   Key words: Bile duct, ito cell, broiler